Intra-Regional Glu-GABA vs Inter-Regional Glu-Glu Imbalance: A 1H-MRS Study of the Neurochemistry of Auditory Verbal Hallucinations in Schizophrenia. (18th October 2019) - Hjelmervik, Helene; Craven, Alexander R; Sinceviciute, Igne; Johnsen, Erik; Kompus, Kristiina; Bless, Josef J; Kroken, Rune A; Løberg, Else-Marie; Ersland, Lars; Grüner, Renate; Hugdahl, Kenneth
Abstract: Glutamate (Glu), gamma amino-butyric acid (GABA), and excitatory/inhibitory (E/I) imbalance have inconsistently been implicated in the etiology of schizophrenia. Elevated Glu levels in language regions have been suggested to mediate auditory verbal hallucinations (AVH), the same regions previously associated with neuronal hyperactivity during AVHs. It is, however, not known whether alterations in Glu levels are accompanied by corresponding GABA alterations, nor is it known if Glu levels are affected in brain regions with known neuronal hypo-activity. Using magnetic resonance spectroscopy (MRS), we measured Glx (Glu+glutamine) and GABA+ levels in the anterior cingulate cortex (ACC), left and right superior temporal gyrus (STG), and left inferior frontal gyrus (IFG), in a sample of 77 schizophrenia patients and 77 healthy controls. Two MRS-protocols were used. Results showed a marginally significant positive correlation in the left STG between Glx and AVHs, whereas a significant negative correlation was found in the ACC. In addition, high-hallucinating patients as a group showed decreased ACC and increased left STG Glx levels compared to low-hallucinating patients, with the healthy controls in between the 2 hallucinating groups. No significant differences were found for GABA+ levels. It is discussed that reduced ACC Glx levels reflect an inability of AVH patients to cognitively inhibit their "voices" through neuronal hypo-activity, which in turn originates from increased left STG Glu levels and neuronal hyperactivity. A revised E/I-imbalance model is proposed where Glu-Glu imbalance between brain regions is emphasized rather than Glu-GABA imbalance within regions, for the understanding of the underlying neurochemistry of AVHs.